Innovation and preservation of traditional values: development of distinctive nusantara batik motifs in women's swimwear design using digital printing techniques - Wesnina Wesnina; Yoga Matin Albar (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This research examines the application of contemporary Nusantara batik motifs to women's swimwear using digital printing techniques, with a specific focus on measuring product dimensions, design elements, and design principles. The study employed a mixed-methods approach combining quantitative surveys with expert panel assessments. Data were collected from five design and textile experts and 100 female respondents aged 18-25 years through validated instruments measuring three key variables: product dimensions (functionality, aesthetics, comfort), design elements (form, color, texture), and design principles (balance, harmony, proportion). Statistical analysis using PLS-SEM revealed that both product dimensions (β=0.482, t=7.171, p<0.001) and design elements (β=0.424, t=6.327, p<0.001) significantly influence the acceptance of design principles in batik-inspired swimwear. The highest consumer acceptance was for the